Evaluation of retinal and choroidal changes in patients with Alzheimer’s type dementia using optical coherence tomography angiography - Ze-Bing Li (International Journal of Ophthalmology, 2021)
AIM: To evaluate the changes in fundus parameters in patients with Alzheimer's type dementia (ATD) using optical coherence tomography angiography (OCTA), to record flash electroretinograms (ERG) using the RETeval system and to explore changes in retinal function. METHODS: Twenty-nine patients with ATD and 26 age-matched normal subjects were enrolled. All subjects underwent OCTA scans to analyse the superficial retinal vessel parameters in the macular area, including the vessel length density, the vessel perfusion density and the area of foveal avascular zone (FAZ), as well as the choroidal thickness. The differences between the patients with ATD and the normal control group were compared and explored the relevant factors affecting vessel parameters. We also recorded the flash ERGs using the RETeval system and intended to explore changes in retinal function by analysing the ERG image amplitude in patients with ATD. RESULTS: The vessel parameters [Pvessel length density=0.005 and Pvessel perfusion density=0.006) and average choroid thickness (P<0.001) in the macular area of the ATD group was less than the control group. The FAZ area was statistically significantly enlarged in the ATD group (P<0.001). These parameters were correlated with the Mini-Mental State Examination (MMSE) score and the Montreal Cognitive Assessment (MoCA). CONCLUSION: Patients with ATD exhibit decreases in the parameters associated with fundus. In addition, these indicators significantly correlate with the MMSE score and the MoCA score. OCTA may be an adjunct tool with strong potential to track changes in the diagnosis and monitoring the progression of the disease.